Cesarean rates according to the Robson classification: analysis in a municipal maternity in São Paulo - Ramos,Gabriela Guimarães Franco (2022)
ABSTRACT Objective To investigate the distribution of parturients at Hospital Municipal da Vila Santa Catarina Dr. Gilson de Cássia Marques de Carvalho according to the Robson classification, identify the cesarean rate in each Robson Group, and understand which group contributes more to the prevalence of Cesarean sections. Methods This is a retrospective observational cross-sectional study conducted through the analysis of medical records of parturients admitted to Hospital Municipal da Vila Santa Catarina Dr. Gilson de Cássia Marques de Carvalho from October 2016 to August 2019. Results A total of 9,794 births were recorded, and 31% were by Cesarean section. The most prevalent Robson Groups were Group 3 (25.7%-2,519), 1 (22.8%-2,234), and 5 (20.5%-2,006). The relative contribution of Cesarean sections was greatest in Groups 5 (39%), 2 (18%), and 1 (12.5%). Conclusion This study demonstrated the Robson classification is useful to lead to a more critical view, identifying the groups that deserve more attention, since they are the major contributors to cesarean rates; hence, the management protocols could be modified aim to reduce cesarean rates.